KOLABORASI ORANG TUA DAN GURU DALAM MEMBENTUK GENERASI TANGGUH MELALUI KAJIAN PARENTING - Rismanda, Endar; Khasanah, Uswatun; Susanti, Agus; Bahri, Saiful; Baharudin, Baharudin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to describe the collaboration of parents and teachers in forming a resilient generation through a parenting study program at MA Darul Huffaz Lampung, as a response to the importance of synergy in education. Using a qualitative approach with a case study type, the research stages involve collecting primary data through observation and interviews with the head of the implementation, teachers, parents, and students, as well as secondary data from the literature. Data analysis uses the Miles and Huberman model, which is strengthened by triangulation of sources and methods to increase credibility. The main findings indicate that the routine parenting study program is an effective forum for communication, education, and friendship, realizing collaboration through the active involvement of teachers in the implementation and participation of parents as participants. Positive impacts were identified in increasing students' mental, moral, spiritual, and intellectual resilience, which was achieved through parenting methods such as role models and habits. Supporting factors include foundation support and participant enthusiasm, while obstacles include distance and parents' busyness. It is concluded that the collaboration of parents and teachers through parenting studies is effective as a strategy for forming a resilient generation in the context of Islamic boarding schools. ABSTRAKPenelitian ini bertujuan mendeskripsikan kolaborasi orang tua dan guru dalam membentuk generasi tangguh melalui program kajian parenting di MA Darul Huffaz Lampung, sebagai respons terhadap pentingnya sinergi dalam pendidikan. Menggunakan pendekatan kualitatif dengan jenis studi kasus, tahapan penelitian melibatkan pengumpulan data primer melalui observasi dan wawancara dengan ketua pelaksana, guru, orang tua, dan siswa, serta data sekunder dari literatur. Analisis data menggunakan model Miles dan Huberman, yang diperkuat dengan triangulasi sumber dan metode untuk meningkatkan kredibilitas. Temuan utama menunjukkan bahwa program kajian parenting yang rutin menjadi wadah efektif untuk komunikasi, edukasi, dan silaturahim, mewujudkan kolaborasi melalui keterlibatan aktif guru dalam pelaksanaan dan partisipasi orang tua sebagai peserta. Dampak positif teridentifikasi pada peningkatan ketangguhan mental, moral, spiritual, dan intelektual siswa, yang dicapai melalui metode pengasuhan seperti keteladanan dan pembiasaan. Faktor pendukung meliputi dukungan yayasan dan antusiasme peserta, sementara kendala mencakup jarak dan kesibukan orang tua. Disimpulkan bahwa kolaborasi orang tua dan guru melalui kajian parenting efektif sebagai strategi pembentukan generasi tangguh dalam konteks pesantren.